Concomitant bladder tumor is a risk factor for bladder recurrence but not upper tract - Liu, Kang; Zhao, Hongda; Alvarez-Maestro, Mario; Gravas, Stavros; Van Renterghem, Koen; Zeng, Guohua; Ng, Chi-Fai; del Pilar Laguna Pes, Maria; Teoh, Jeremy Yuen-Chun; de la Rosette, Jean J. M. C. H. (MDPI, 2022)
Objective: To evaluate the clinical outcomes of UTUC patients with or without concurrent bladder tumor. Design, Setting, and Participants: The Clinical Research Office of the Endourology Society-Urothelial Carcinomas of the Upper Tract (CROES-UTUC) Registry included 1134 UTUC patients with or without concurrent bladder tumor treated between 2014 and 2019. Results: In 218 (19.2%) cases, concurrent bladder tumor was present, while in 916 (80.8%) patients, no bladder cancer was found. In the multivariable Cox regression analysis, concomitant bladder tumor (hazard ratio (HR) 1.562, 95% confidence interval (CI) 0.954-2.560, p = 0.076) indicated a trend associated with recurrence-free survival for UTUC. Further data dissection confirmed that concomitant bladder tumor is a risk factor of bladder recurrence (HR 1.874, 95% CI 1.104-3.183, p = 0.020) but not UTUC recurrence (HR 0.876, 95% CI 0.292-2.625, p = 0.812). Kidney-sparing surgery (KSS) (HR 3.940, 95% CI 1.352-11.486, p = 0.012), pathological T staging >= pT2 (HR 2.840, 95% 1.039-7.763, p = 0.042) were significantly associated with UTUC recurrence. KSS does not affect bladder recurrence (HR 0.619, 95% CI 0.242-1.580, p = 0.315). A limitation is the retrospective nature of the present study analysis. Conclusions: The presence of concomitant bladder tumor does not increase risk of UTUC recurrence, but it results in an increased risk of bladder recurrence. KSS does not affect bladder recurrence and can still be considered in patients with concomitant bladder tumor.
Keywords: Concomitant Bladder Tumor; Kidney-Sparing Surgery; Recurrence-Free Survival; Upper Tract Urothelial Carcinoma